GWAS and polygenic risk score of severe COVID-19 in Eastern Europe - Elena Kovalenko; Layal Shaheen; Ekaterina Vergasova; Alexey Kamelin; Valerya Rubinova; Dmitry Kharitonov; Anna Kim; Nikolay Plotnikov; Artem Elmuratov; Natalia Borovkova; Maya Storozheva; Sergey Solonin; et al. (Frontiers in Medicine, 2024)
BackgroundCOVID-19 disease has infected more than 772 million people, leading to 7 million deaths. Although the severe course of COVID-19 can be prevented using appropriate treatments, effective interventions require a thorough research of the genetic factors involved in its pathogenesis.MethodsWe conducted a genome-wide association study (GWAS) on 7,124 individuals (comprising 6,400 controls who had mild to moderate COVID-19 and 724 cases with severe COVID-19). The inclusion criteria were acute respiratory distress syndrome (ARDS), acute respiratory failure (ARF) requiring respiratory support, or CT scans indicative of severe COVID-19 infection without any competing diseases. We also developed a polygenic risk score (PRS) model to identify individuals at high risk.ResultsWe identified two genome-wide significant loci (P-value <5 × 10−8) and one locus with approximately genome-wide significance (P-value = 5.92 × 10−8-6.15 × 10−8). The most genome-wide significant variants were located in the leucine zipper transcription factor like 1 (LZTFL1) gene, which has been highlighted in several previous GWAS studies. Our PRS model results indicated that individuals in the top 10% group of the PRS had twice the risk of severe course of the disease compared to those at median risk [odds ratio = 2.18 (1.66, 2.86), P-value = 8.9 × 10−9].ConclusionWe conducted one of the largest studies to date on the genetics of severe COVID-19 in an Eastern European cohort. Our results are consistent with previous research and will guide further epidemiologic studies on host genetics, as well as for the development of targeted treatments.